Pain in newborns: a descriptive study about assessment and non-pharmacological treatment at a NICU - Flávia de Souza Barbosa; Ianê Nogueira do Valle (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Introduction: According to contemporary knowledge about pain, every painful stimulus is generated, transmitted and interpreted in the same way for newborns and adults. Newborns have all the anatomical, functional and neurochemical elements necessary to nociception. Nevertheless, the manifestation and communication of pain in newborns are different from adult people, demanding other physiological and behavioral indicators to assess it. Objective: To identify, among nurses and physicians, their knowledge, beliefs and practices regarding assessment, non-pharmacological treatment and other measures to relieve-treat pain in newborns. Methods: Descriptive and exploratory stud of 16 doctors and 27 nurses (86,0% of staff) who work in a neonatal intensive care unit belong to a university hospital in São Paulo, Brasil. The date were collected through a questionnaire with open and closed questions, and underwent Kappa, Chi-Square and Fischer tests, in order to verify associations and agreements among the answers. Results and conclusions: The interviewed professionals believe that newborns actually feel pain. They recognize its importance and refer performing frequent evaluations of pain status, although demonstrating poor practice identify newborn pain from physiological or behavioral treatment of pain: the professionals know some important measures, but do not make use of then in theirs practices. There was no significant association between spontaneous and directive answers, regarding physiological and behavioral signs of pain.